Identification of Glass Powder Effect for Filler Composition in Hot Roller Sheet "“ Wearing Course (HRS-WC) Mixture - Ammar, Nur; Azwansyah, Heri; Mayuni, Siti (Jurnal Teknik Sipil, 2025)
This study examines the use of glass powder as a filler substitute in Hot Rolled Sheet"“Wearing Course (HRS-WC) asphalt mixtures to enhance performance and promote waste utilization. The research employed an experimental method following SNI and AASHTO standards, testing mixtures with 0%, 25%, 50%, 75%, and 100% glass powder substitution using the Marshall method. Results showed that 50% and 75% substitution levels produced the best performance in terms of stability and Marshall Quotient, while 100% substitution led to a decline due to the glass powder"™s inability to absorb asphalt. Increased glass powder content also reduced VIM values, indicating denser mixtures, although at 100% substitution, both VIM and VMA exceeded specification limits. The findings suggest that glass powder can be effectively used as a partial filler replacement, with optimal results achieved at 50"“75% substitution and 5"“7% asphalt content.